Power output and pacing during international cross-country mountain bike cycling - Granier, C.; Abbiss, C. R.; Aubry, A.; Vauchez, Y.; Dorel, S.; Hausswirth, C.; Le Meur, Y. (International Journal of Sports Physiology and Performance, 2018)
Purpose: To characterize the physiological profiles of elite cross-country mountain-bike (XCO-MTB) cyclists and to examine their pacing and power-output (PO) distribution during international races. Methods: Over 2 competitive seasons, 8 male XCO-MTB cyclists (VO2max 79.9 [5.2] mL/min·kg, maximal aerobic power [MAP] 411 [18] W and 6.3 [0.4] W/kg) regularly undertook incremental tests to assess their PO and heart rate (HR) at first and second ventilatory thresholds (VT1 and VT2) and at VO2max. During the same period, their PO, HR, speed, and cadence were recorded over 13 international races (total of 30 recorded files). Results: Mean PO, speed, cadence, and HR during the races were 283 (22) W (4.31 [0.32] W/kg, 68% [5%] MAP), 19.7 (2.1) km/h, 68 (8) rpm, and 172 (11) beats/min (91% [2%] HRmax), respectively. The average times spent below 10% of MAP, between 10% of MAP and VT1, between VT1 and VT2, between VT2 and MAP, and above MAP were 25% (5%), 21% (4%), 13% (3%), 16% (3%), and 26% (5%), respectively. Both speed and PO decreased from the start loop to lap 1 before stabilizing until the end of the race.Conclusions: Elite off-road cyclists demonstrated typical values of world-class endurance cyclists with an excellent power-to-mass ratio. This study demonstrated that XCO-MTB races are performed at higher intensities than reported in previous research and are characterized by a fast start followed by an even pace.